Synthesis of praziquantel via N-acyliminium ion cyclization of amido acetals through several synthetic routes - Kim, JH; Lee, YS; Kim, CS (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
Syntheses of praziquantel have been accomplished via an N-acyliminium ion by several routes including the tandem nucleophilic addition-cyclization sequence from amido acetal (8) or (10) and a stepwise cyclization of enamide (9) generated from the nucleophilic addition reaction of amido acetal (8) or (10).
Keywords: ASYMMETRIC-SYNTHESIS; (+/-)-3-DEMETHOXYERYTHRATIDINONE